Classification of Drug Usage Patterns and Identification of Diseases in the Provision of Drug Types Using the K-Nearest Neighbors Method - Rafi Farizki; Nano Supriatna; Christine Juliana (Riviera Publishing, 2024)
The increasing complexity of healthcare systems highlights the need for data-driven approaches to optimize drug usage patterns and improve disease management. This study employs the K-Nearest Neighbors (KNN) algorithm to analyze correlations between prescribed medications and associated diseases, utilizing a dataset comprising attributes such as patient demographics, drug types, dosages, and treatment frequencies. The results reveal significant trends, including the predominance of